The Marketing Strategy of Beverage Business Atzalzia Soy Milk in Bengkulu City - Ayu Nopia Erniati; Sri Handayani; Tito Irwanto (Penerbit Jurnal Indonesia, 2021)
The aims of this study is to identify the internal and external factors, to determine the strategic priorities and also to formulate the alternative strategies that can be applied to sell Zalzia Soy Milk in Bengkulu City. This is a qualitative study that took 55 respondents as the sample. In order to collect the data, the writers used questionnaires and documentation which then analyzed by using SWOT Analysis. From the results of the study, it was found that IFAS and EFAS, the strength of the Zalzia Soy Milk Business in Bengkulu City was 37.82 while the weakness was 1.24 so the cell (quadrant) of internal factors was 37.82 - 1.24 = 36.58. Moreover, the opportunities possessed the strategy is 27.04 with a threat of 16.13 so the cell (quadrant) of external factors is 27.04 - 16.13 = 10.91 which is in quadrant cell 1 on the SWOT analysis diagram. Finally, the aggressive marketing strategy that can be used is to improve the taste, quality and quantity of the product and also to recognize the characteristics of the marketing environment.